Family demographic processes and in-work poverty: A systematic review - Antonino Polizzi; Emanuela Struffolino; Zachary Van Winkle (Advances in Life Course Research, 2022)
This article reviews ever published quantitative evidence on in-work poverty and family demographic processes in OECD and EU-28 countries. Despite the increasing attention to in-work poverty in Europe and beyond, a comprehensive and critical review on how family demographic processes shape in-work poverty risks is still missing. In this systematic review, we first provide a quantitative review of results from analyses that estimated the association between in-work poverty and parental home leaving, union formation, marriage, parenthood, and dissolution of non-marital and marital unions. This allows us to formulate tentative conclusions about whether and in which direction family demographic processes are associated with in-work poverty. Second, we discuss in detail conceptual and methodological advances in in-work poverty research, such as longitudinal analytical designs or attempts to make in-work poverty research more sensitive to policy context, gender, and the life course. Our review highlights theoretical and methodological challenges for future studies linking in-work poverty and family demography.
Keywords: 300; in-work poverty; family demography; systematic review; cross-national